(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Varicocele is by far the most commonly performed operation for the treatment of male infertility. Varicocele is found in approximately 15% of the general population, 35% of men with primary infertility, and 75% to 81% of men with secondary infertility. Methods: A prospective and retrospective clinical descriptive study of 32 patients with varicocele who were diagnosed and treated by microsurgical varicoceletomy at Can Tho Central General Hospital from March 2015 to July 2019. Results: Symtoms: scrotal paint 59,4%, infertility 31,3%, scrotal paint and infertility 9,4%. Left scrotal pain 86,4%, both scrotal pain 13,6%. Varicocele grade III 71,9% and grade II 28,1%. Scrotal untrasound detected 75% cases. 77,3% complete resolution of pain, 22,7% a partial resolution of pain. Natural pregnancy rate 53,8%. There were neither intraoperative nor postoperative complications. Conclusions: Varicocele’s diagnosis depends on clinical. Microsurgical varicoceletomy is a safe, effective approach in treatment scrotal pain and infertility.